Design of instrumentation for control and safety rod drive mechanisms of prototype fast breeder reactor. (1st January 2013) - Dheenadhayalan, R.; Venkatesan, A.; Madhusoodanan, K.; Chellapandi, P.
Prototype Fast Breeder Reactor (PFBR) is a 500 MWe, sodium cooled, plutonium oxide-uranium oxide fuelled, pool type fast breeder nuclear reactor under construction in India. Control and Safety Rod Drive Mechanism (CSRDM) is part of one of the shutdown systems and is used to drive neutron absorber rods up and down. Instrumentation and control for CSRDM realises significant functions like power control, power set back and controlled shutdown. A study was carried out into incidents during the operation of 40 MWt experimental reactor called Fast Breeder Test Reactor and testing of a prototype CSRDM. Significant incidents in FBTR like uncontrolled withdrawal of absorber rod, movement in unintended direction, partial absorber rod drops are found to have occurred. Corrective measures are taken in the I&C of PFBR. PFBR I&C for CSRDM is presented. I&C designers for nuclear systems may gainfully make use of the experiences described in the paper.